Teaching Arabic by Using Google Meet at Ma'had 'Aly Ar Raayah Sukabumi, Indonesia - Mulyadi Mulyadi; Arif Taufikurrohman; R. Taufiqurrochman; Firman Nurul Fauzi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
One of the things that cannot be hidden from society today is the development and progress of educational facilities, namely progress in the field of educational technology, where many modern technologies have emerged, and their role in the educational process has become a necessity, especially during the spread of the Corona pandemic that swept the world. who have to use these modern means to complete their work, including the educational process. This study aims to describe teaching Arabic through google meet at Ar Raayah College in Sukabumi, Indonesia and to describe the benefits of teaching Arabic at Ar Raayah College. This researcher uses a qualitative descriptive method. The results of this study are as follows: Google meet is useful in teaching Arabic during the spread of the Corona pandemic, and the Arabic language teaching method using Google meet requires the participation of three elements, namely: the Google program supervisor, subject teachers, and students.